Control design for a bionic kangaroo. (September 2015) - Graichen, Knut; Hentzelt, Sebastian; Hildebrandt, Alexander; Kärcher, Nadine; Gaißert, Nina; Knubben, Elias
Abstract: This contribution describes the control design for the BionicKangaroo, a bionic demonstrator developed by the Festo Bionic Learning Network to resemble the unique hopping characteristics of the kangaroo. The robot uses hip and tail actuation as well as pneumatic actuators in combination with elastic tendons in the leg kinematics. Nonlinear controllers are designed for the flight and stance phases and a switching condition is derived that initiates the next hopping cycle. The flight phase controller consists of an adaptive feedforward control based on the nonlinear flight dynamics. A state feedback part stabilizes the kangaroo along the flight trajectories. For the stance phase, a model-based pressure controller is designed for the individual legs to compensate for roll movements or disposals during the hopping cycle. Experimental results as well as energy considerations show the performance of the control design for the BionicKangaroo.